Choiced Issues of Realisation of Speech Units in Stuttering - Chęciek, Mieczysław (Logopedia Silesiana, 2015)
The author in his paper attempts at answering a question concerning the relationship between dysfluent realisation of speech units (sound, open and closed syllable, word, phrase and sentence) and disordered symptoms occuring beyond the language (e.g. the speed of speech, symptoms of logophobia/anxiety, muscle comovements) and the age of the stutterers. The significant quantative and qualitative differences, being prototypes for the age groups are also discussed. It will be in three age groups (A: 7-11 yrs.; B: 12-16; C: 17 yrs. and more) at the number of 250 stutterers discussed. The findings of the study suggest the assumption that frequency of occurrence of dysfluent realisation of speech units among stutterers in three groups is very similar. The units that are most commonly blocked occur in initial sound, alike in all groups and stop-explosive consonants and vowels belong to the most fre¬quen¬tly blocked ones. The highest ratio of frequency in stuttering in percentage is slight level of stuttering for all groups. Significant differences between groups in case of logophobia/anxiety level have been observed, but this is not discussed in this paper.